Pengaruh Edukasi mengenai Makanan Pendamping Air Susu Ibu dengan Buku Kesehatan Ibu dan Anak Revisi 2015 terhadap Pengetahuan dan Sikap Ibu dalam Pemberian Makanan Pendamping Air Susu Ibu di Kecamatan Pontianak Barat - Ridha Hasanah; Muhammad In'am Ilmiawan; Rini Andriani (Jurnal Kesehatan Indonesia, 2023)
Complementary food is nutritious food and drink as a transition from breast milk to family food. The positive and negative aspects are contained in one's knowledge and will determine one's attitude. The 2015 revised Maternal and Child Health handbook contains records of maternal and child health to maintain and care for maternal and child health. The objective of this research is determine the effect of education on complementary feeding with the 2015 revised Maternal and Child Health handbook on mothers’ knowledge and attitude of complementary feeding in West Pontianak District. This is a quasi experimental research with a one group pretest-posttest design. Taking 66 samples with consecutive sampling. Knowledge and attitude questionnaires and material evaluation sheets are used as measuring tools. Data analysis use paired sample t-test with the wilcoxon signed-rank test as an alternative test. There were 12 mothers who had a moderate level of knowledge before education, then increased to 21 mothers after education. The results of the wilcoxon signed-rank test obtained the sig. value < 0.05. The mothers’ attitude in terms of complementary feeding and feeding rules are changed between before and after education. Education with the 2015 revised Maternal and Child Health handbook had a significant effect on increasing the category of mothers' knowledge of complementary food and changing mothers' attitude in feeding rules. However, it is still necessary to add material based on the latest scientific evidence in the 2015 revised Maternal and Child Health handbook.